On quadruples of linearly connected projections and transitive systems of subspaces - Moskaleva, Yu. P.; Ostrovskyi, V. L.; Yusenko, K. A. (Methods of Functional Analysis and Topology, 2007)
We study conditions under which the images of irreducible quadruples of linearly connected projections give rise to all transitive systems of subspaces in a finite dimensional Hilbert space.